Adrenal Crisis with Hypercalcemia Precipitated by Levothyroxine Initiation in a Patient with Polyendocrinopathy - Shwaylia, Fatma; Almazrouei, Raya (Journal of Diabetes and Endocrine Practice, 2024)
Polyglandular autoimmune syndrome type 2 involving autoimmune primary adrenal insufficiency and autoimmune hypothyroidism is rare. Fatigue and tiredness are common overlapping symptoms between the two conditions. Initiating levothyroxine in a patient with underlying adrenal insufficiency may precipitate a severe adrenal crisis. Here, we report a case of a 21-year-old lady who presented with an adrenal crisis with hypercalcemia after levothyroxine initiation. This case highlights the importance of taking a proper detailed history and diligent physical examination which can direct the appropriate diagnosis and avoid the preventable consequence.
Keywords: Addison disease; adrenal crisis; hypercalcemia; hypothyroidism; polyendocrinopathy syndromes